(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Corporate mergers and acquisition has become a highly popular strategy in recent years. Thus, much attention has been focused on its outcomes. It has served as a substitute for innovation, a greater means of diversification. The banking sector is often referred to as an engine growth of the economy. The intermediation role which the sector plays in national development cannot be overemphasized. Thus, given the recent consolidation exercise in the Nigerian banking sector, we explored the impact of mergers and acquisition on managerial commitment in this paper. We adopted the descriptive survey method and primary data were obtained using oral interview and questionnaire. The population of this study comprised all consolidated banks in Nigeria and the total sample size for this study was 384 respondents from commercial banks in South East Nigeria. The Chi-square (X2) non-parametric statistic was used to test the hypotheses. The results revealed that mergers and acquisitions have significant positive effect on managerial role and commitment of managers of commercial banks in Nigerias South East Region. We, therefore, recommend that incentive measures such as improved pay and good working environment should be promoted in commercial banks during mergers and acquisitions as these will further enhance managerial commitment.